Lingual Thyroid: Case report and brief review of the literature - Thomas Fakadej, BS; Aneri B Balar, MD; Sriharsha Kota, DO; Dhairya A. Lakhani, MD; Joe T Joseph, MD (Radiology Case Reports, 2023)
Lingual thyroid is by far the most common presentation of ectopic thyroid. Though mostly asymptomatic it is associated with congenital hypothyroidism and importantly, absence of orthotopic thyroid making it the only functional thyroid tissue a patient has in many cases. It appears indistinguishable to orthotopic thyroid tissue on imaging, with avid homogeneous enhancement on contrast computed tomography. Here we report clinical presentation and imaging findings of lingual thyroid in a 38-year-old man.